Pedalium murex Linn.: An overview of its phytopharmacological aspects - Patel D.K.; Laloo D.; Kumar R.; Hemalatha S. (My University, 2025)
Pedalium murex Linn (family: Pedaliaceae) (P. murex) commonly known as Large Caltrops and Gokhru (India) is a shrub found in the Southern part, Deccan region of India and in some parts of Ceylon. Different parts of the plant are used to treat various ailments like, cough, cold and as an antiseptic. Interestingly, P. murex is reported traditionally to have an excellent cure in patients with reproductive disorders which are mainly impotency in men, nocturnal emissions, gonorrhoea as well as leucorrhoea in women. The plant has also benifited in complications like urinary track disorder as well as gastro intestinal tract disorders. Phytochemically the plant is popular for the presence of a considerable amount of diosgenin and vanillin which are regarded as an important source and useful starting materials for synthesizing steroidal contraceptive drugs and isatin alkaloids. Other phytochemicals reported in the plant includes quercetin, ursolic acid, caffeic acid, amino acids (glycine, histidine, tyrosine, threonine, aspartic acid and glutamic acid) and various classes of fatty acids (triacontanoic acid, nonacosane, tritriacontane, tetratriacontanyl and heptatriacontan-4-one). Pharmacologically, the plant have been investigated for antiulcerogenic, nephroprotective, hypolipidemic, aphrodisiac, antioxidant, antimicrobial and insecticidal activities. From all these reports it can be concluded that the plant were found to have a better profile with potential natural source for the treatment of various range of either acute or chronic disease. The overall database of our review article was collected from the scientific sources in regards with all the information of the research article for P. murex published so far. © 2011 Hainan Medical College.